2008
DOI: 10.1590/s0100-879x2008001200013
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of chronic diabetic complications and metabolic syndrome is not associated with maternal type 2 diabetes

Abstract: The maternal history of type 2 diabetes mellitus (DM) has been reported more frequently in patients with type 2 DM than paternal history. The aim of the present study was to determine if there was an association between maternal history of DM and the presence of chronic complications or metabolic syndrome (MetS) in patients with type 2 DM. A cross-sectional study was conducted with 1455 patients with type 2 DM. All outpatients with type 2 diabetes attending the endocrine clinics who fulfilled the eligibility c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…The contribution of family history type of T2D on lipids has been controversial in both diabetics and nondiabetics [4,6,10,11,16]. The results of this study show a greater impact of maternal family history on lipid parameters than paternal family history, which is in accord with a previous study of nondiabetic South East Asians, composed of 68 % Chinese, 18 % Malays, and 14 % Asian Indians [6].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The contribution of family history type of T2D on lipids has been controversial in both diabetics and nondiabetics [4,6,10,11,16]. The results of this study show a greater impact of maternal family history on lipid parameters than paternal family history, which is in accord with a previous study of nondiabetic South East Asians, composed of 68 % Chinese, 18 % Malays, and 14 % Asian Indians [6].…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have shown a predominance of maternal family history of T2D in patients [4,[9][10][11]. The proposed explanations for excess maternal transmission of T2D include mitochondrial DNA mutations [12], intrauterine environment [13], and behavioral influence of the mother [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation